2002
DOI: 10.1002/hep.1840360614
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant monoclonal IgA anti—PDC-E2 autoantibodies derived from patients with PBC

Abstract: Primary biliary cirrhosis (PBC) is an autoimmune liver disease characterized by the presence of autoantibodies to mitochondria (AMA). Recent evidence suggests that PBC develops after a locally driven response in the mucosa, where immunoglobulin A (IgA) is the dominant antibody isotype. In this study, we produced recombinant pyruvate dehydrogenase complex (PDC-E2)-specific dimeric human IgA monoclonal antibodies (mAbs) in a baculovirus expression system. By using 2 anti-PDC-E2 IgG mAbs derived from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The development of recombinant IgA was not beneficial to this work due to the low yield of expression systems. 10 New technology using the Sap peptide for the isolation and purification of functionally intact IgA has enabled new studies concerning the role of this Ig isotype in mucosal disease. 11 For the assay system, we chose the pIgR expressing MDCK cell model because a significant body of data already exists on the use of IgA against HIV and Rota virus in infected cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of recombinant IgA was not beneficial to this work due to the low yield of expression systems. 10 New technology using the Sap peptide for the isolation and purification of functionally intact IgA has enabled new studies concerning the role of this Ig isotype in mucosal disease. 11 For the assay system, we chose the pIgR expressing MDCK cell model because a significant body of data already exists on the use of IgA against HIV and Rota virus in infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Media consisted of DMEM supplemented with 10% fetal calf serum (FCS). 9,10 The inserts were composed of thin membranes of polyethylene terephthalate with 1.0 m pores, 1.6 ϫ 10 6 pores/cm 2 . The cell cultures were maintained at 37°C with 5% CO 2 in a humid incubator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot preclude the possibility that the apical staining obtained with anti-PDC-E2 monoclonal antibodies may be secondary to the presence of immune complexes formed by secreted IgA and AMA antigens, as one line of evidence seems to suggest. 100 Apoptosis of biliary epithelial cells in PBC warrants further discussion and may prove crucial for immune tolerance breakdown, 63,101 as illustrated under other conditions. Quite surprisingly, Odin et al first demonstrated that PDC-E2 remains intact and retains its immunogenicity during cholangiocyte apoptosis because of a cell-specific lack of glutathionylation of biliary epithelial cells.…”
Section: Pbc Pathogenesismentioning
confidence: 99%
“…Several immunoglobulin isotypes from many different species, including murine IgG, 2,3,[21][22][23][24][25] chimeric IgG, [26][27][28][29][30] human IgG, [31][32][33][34][35][36][37][38][39] IgA, [40][41][42] IgM 41 and IgE, [43][44][45] as well as pig Igs 30,45 have been successfully expressed in insect cells. These molecules are all correctly processed (signal peptide cleaved), glycosylated and assembled (H2L2) with a production rate varying from 0.75 to 100 mg/l, depending on the antibody ( …”
Section: Introductionmentioning
confidence: 99%